Takot ako the dynamics of abjection and the concept of fear in the Philippine horror television series, Oka2kat - Maniago, Sarah Jean Pallasigui 1992-; Guieb, Eulalio III; University of the Philippines. College of Mass Communication (2013)
"This study bears from the exploration of the dynamics of abjection and the concept of fear in Philippine horror television. This study is divided into two main concepts: (1) fear and (2) abjection. It aims to relate these two concepts using all thirteen (13) episodes of the Philippine horror television series, Oka2kat, as sampling and each episode as the unit of analysis. Using content analysis with a qualitative approach, the elements deemed fearful in this horror television series are classified under some variables or themes of abjection. This study uses Noel Carroll's (199) physical dimensions of fear as a framework for the indicators of fear. These indicators, which are formulated based on Carroll's aforementioned premise, consist of: (1) when the character screams or is shocked; (2) when a character seems scared by shuddering, freezing or tensed; (3) when a character experiences revulsion or disgust; and (4) when a character threatens or warns in the presence of these elements. Using Kristeva's theory of abjection (1982) as a framework of analysis, these fearful elements are related with the concept of abjection they fall under. These variables, which are pre-determined, include: (1) the woman as a "monstrous-feminine"; (2) the unclean; (3) that which disturbs the social order; (4) the "old and long familiar (Freud as cited in Creed, 1993); and (5) the confrontation of the abject."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Fear; Fear in motion pictures; Horror television programs -- Philippines